Peran Kepemimpinan Kepala Sekolah Perempuan dalam Meningkatkan Kinerja Guru di SDN 4 Banjaranyar Ciamis - Rina Marliani; Neneng Nurmalasari (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
This research aims to examine the leadership role of female school principals in improving teacher performance at the Banjaranyar Ciamis State Elementary School 4, using the EMASLIM framework (Educator, Manager, Administrator, Supervisor, Leader, Innovator, Motivator). This research uses a qualitative approach with a case study method. Data was collected through interviews, observation and documentation studies. The results of the research show that the female principal at SDN 4 Banjaranyar Ciamis succeeded in carrying out a leadership role within the EMASLIM framework well. He not only acts as an Educator by continuously developing himself and encouraging a positive learning culture, but also as an effective Manager in managing school resources. Apart from that, he also demonstrated the ability to be a reliable Administrator in managing school administration, a visionary Leader in developing the school's vision and mission, an Innovator who encourages learning innovation, and a Motivator who is able to motivate teachers and staff. The success of the principal in carrying out this leadership role contributed significantly to improving teacher performance at SDN 4 Banjaranyar Ciamis.